Analysis of shock deceleration effects in the NASA electric arc shock tube - Collen, PL; Di Mare, L; McGilvray, M; Satchell, M (American Institute of Aeronautics and Astronautics, 2023)
Complex processes related to nonequilibrium thermochemistry and radiation are a fundamental aspect of atmospheric entry flowfields. Shock tubes provide a means of generating test gas conditions analogous to those found on the stagnation line of flight shock layers, which allows extraction of thermochemical rates and radiative intensities. Currently, the NASA Electric Arc Shock Tube (EAST) is the best source of such data. Although simple in principle, nuances of these experimental facilities can affect the observed results. Notably, electron densities and radiance levels in excess of equilibrium predictions have been observed at EAST for many years. The deceleration of the shock as it passes along the tube has been posited as a source of these discrepancies. In this work, a recently developed numerical methodology (LASTA) is applied to these results from the literature. Using the experimental shock speed profile as an input, trends in postshock electron density are computed. Radiance throughout the shock layer is also predicted by coupling the simulation to the NASA NEQAIR code. It is shown that the predictions of LASTA provide a good match to the magnitudes and trends of the experimental differences, confirming shock speed deceleration as their cause.